Bilateral Sterile Pyogranulomatous Keratitis in a Dog - Michael C. Rahe; Aubrey Cordray; Joseph Haynes (Case Reports in Veterinary Medicine)
Purpose. To describe the clinicopathologic features of bilateral sterile pyogranulomatous keratitis in a 16-year-old spayed female rat terrier dog. Methods. The dog presented one year prior due to ulceration of the right and left corneas. The ulcers healed but plaques developed on both eyes which progressed, during the course of one year, to cover both the left and the right corneas. Due to the animal’s loss of sight and its painful condition, bilateral enucleation was performed with submission of the eyes for histopathology. Results. Microscopic examination revealed bilateral pyogranulomatous keratitis absent of etiological organisms. Conclusions. To the authors’ knowledge, this is the first documented case of bilateral sterile pyogranulomatous keratitis in a dog.